Electromagnetic and eddy current NDT in weld inspection: a review - Gao, P; Wang, C; Li, Y; Cong, Z (Insight (Northampton), 2015)
Defects in welds always undermine the reliability of the overall structure, potentially causing serious structural failures. Electromagnetic and eddy current testing (ECT) are widely used in weld inspection because of their advantages, such as rapidity, they are non-contact and they do not require a coupling agent. This paper presents a review of the development of electromagnetic and eddy current non-destructive testing (NDT) in fusion welding and friction stir welding (FSW). In the section on fusion weld inspection, the review includes probe improvement, the multi-frequency eddy current technique, signal processing and computational inversion techniques. In the section on friction stir welding, the review shows the probe structure design and the application of the pulsed eddy current (PEC) and SQUID-based eddy current techniques. Finally, the future development of ECT in welding inspection is discussed in the last part of the paper.